2022
DOI: 10.3390/v14102154
|View full text |Cite
|
Sign up to set email alerts
|

(+)-Usnic Acid and Its Derivatives as Inhibitors of a Wide Spectrum of SARS-CoV-2 Viruses

Abstract: In order to test the antiviral activity, a series of usnic acid derivatives were synthesized, including new, previously undescribed compounds. The activity of the derivatives against three strains of SARS-CoV-2 virus was studied. To understand the mechanism of antiviral action, the inhibitory activity of the main protease of SARS-CoV-2 virus was studied using the developed model as well as the antiviral activity against the pseudoviral system with glycoprotein S of SARS-CoV-2 virus on its surface. It was shown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…Testing on an infectious virus allows us to understand whether the compound has activity against the specified virus, but it does not give an understanding of the mechanism of this agent action. Since the data obtained using infectious virus did not correlate directly with those obtained for the main viral protease 3CLPro and we 24 and other researchers 47 have previously shown that usnic acid derivatives can be the effective inhibitors of entry; our further efforts were focused on studying the biological properties of compounds using the pseudovirus system.…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Testing on an infectious virus allows us to understand whether the compound has activity against the specified virus, but it does not give an understanding of the mechanism of this agent action. Since the data obtained using infectious virus did not correlate directly with those obtained for the main viral protease 3CLPro and we 24 and other researchers 47 have previously shown that usnic acid derivatives can be the effective inhibitors of entry; our further efforts were focused on studying the biological properties of compounds using the pseudovirus system.…”
Section: Resultsmentioning
confidence: 92%
“…The N-terminal domain of the S-protein was considered as a potential biological target. It was shown 24 that a number of usnic acid derivatives could bind to the biliverdin site. 51 The choice of such a binding site was justified by a detailed study of the structure and function of the SARS-CoV-2 surface glycoprotein, as well as by a comparison of the pharmacophore profiles of the binding site and ligands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Effective protease inhibitors were detected using this surrogate test system [18]. In addition, this surrogate model enabled us to elucidate the mechanism of antiviral action of effective SARS-CoV-2 inhibitors, based on natural usnic acid [19]. The inhibitory activity of the synthesized conjugates against the SARS-CoV-2 Mpro was studied in vitro using the previously developed FRET-based enzyme assay (Table 3).…”
Section: Sars-cov-2 Mpro Inhibiting Activitymentioning
confidence: 99%
“…UA and remdesivir (a product recently approved for the treatment of COVID-19) showed a similar activity in a SARS-CoV-2 binding assay [ 44 ]. Finally, an in vitro study performed on Vero E6 cells showed a significant activity of UA against three different strains of SARS-CoV-2, namely Wuhan, Delta, and Omicron [ 45 ].…”
Section: Introductionmentioning
confidence: 99%